Current Development of Mesenchymal Stem Cell-Derived Extracellular Vesicles - Bingyi Zheng; Xueting Wang; Meizhai Guo; Chi-Meng Tzeng (Cell Transplantation)
Mesenchymal stem cells (MSCs) are pluripotent stem cells with self-renewal. They play a critical role in cell therapy due to their powerful immunomodulatory and regenerative effects. Recent studies suggest that one of the key therapeutic mechanisms of MSCs seems to derive from their paracrine product, called extracellular vesicles (EVs). The EVs contain much DNA, messenger RNA (mRNA), microRNA, and protein components, which can exert intracellular communication to target cells. In clinical applications, the MSC-EVs have been widely used in tissue repair and immune disorder diseases. However, there are serval issues need to be considered such as how to accomplish the large-scale production of EVs and how to verify the exact mechanism of EVs. In this review, we summarize the current progress of MSC-EVs and discuss the challenges and future of MSC-EVs.